PENGEMBANGAN PERSEMAIAN BIBIT NANGKA DI JEMBER UNTUK MENDUKUNG KEMANDIRIAN BUAH LOKAL - Arini, Silvia Fitri Mei; Qomariah, Aisatul (PAPUMA: Journal of Community Services, 2026)
The development of a permanent jackfruit nursery in Jember Regency aimed to increase the availability of quality seedlings and support the independence of local products. The activity was carried out in Karangpring Village, Sukorambi District, Jember Regency, specifically at the Jember Nursery. It included site preparation, planting, outreach, and practical programs for farmers, students, and related institutions. This initiative produced high-quality jackfruit seedlings with optimal growth and good viability. Indicators of good jackfruit seedlings are characterized by the diameter and height of the seedlings. These indicators serve as indicators of good jackfruit seedling growth. Farmers gained access to superior seedlings and knowledge of cultivation techniques, practical learning processes, and universities strengthened partnerships as replicable models. Overall, the activities contributed to the independence of Jember's local commodities, strengthened community capacity, food security, and increased economic value.